Evidence of laboratory vector competence of Culex modestus for West Nile virus - Balenghien, Thomas; Vazeille, Marie; Reiter, Paul; Schaffner, Francis; Zeller, Herve; Bicout, Dominique J (Journal of the American Mosquito Control Association, 2007)
During the past 10 years, West Nile virus (WNV) has been responsible for large and severe human outbreaks and horse epizootics through the Old and the New World. Since WNV was first isolated from field-collected mosquitoes of Culex modestus in 1964 in France, this species, which aggressively feeds on birds and mammals, is considered a putative WNV vector in Europe. We report on the first evidence on the laboratory vector competence of Cx. modestus for WNV. To assess this trait, F3 and F4 females from southern France were fed through a membrane with a strain of WNV isolated from a horse in the Camargue (Rhône River delta) in 2000. On day 14 after virus ingestion, 90% of mosquitoes displayed a disseminated infection. WNV was detected in the saliva from 2 of 5 infected mosquitoes selected for testing. These preliminary results demonstrate that Cx. modestus is capable of experimentally transmitting WNV.